2016
DOI: 10.1021/acs.jafc.6b01513
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechin Prevents Hypoxia/Reperfusion-Evoked Oxidative Stress-Regulated Autophagy-Activated Apoptosis and Cell Death in Microglial Cells

Abstract: Defective activation and proliferation in microglial cells has been suggested to be associated with the increase of cerebral ischemia/reperfusion injury. We investigated the protection and molecular mechanism of green tea catechin on hypoxia/reperfusion-induced microglial cell injury in vitro. Microglial cells were cultured in hypoxia condition (O2 < 1%) and then re-incubated to the complete normal culture medium (reperfusion). Hypoxia/reperfusion obviously decreased cell viability and induced apoptosis in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…The tea catechin has the ability to inhibit cell apoptosis and oxidative stress in animal and cell experiments. [53][54][55] A previous animal experiment determined that green or black tea extracts led to a delay of lens opacity progression. 56 This was an interesting observation because tea is very popular around the world, especially in China.…”
Section: Discussionmentioning
confidence: 99%
“…The tea catechin has the ability to inhibit cell apoptosis and oxidative stress in animal and cell experiments. [53][54][55] A previous animal experiment determined that green or black tea extracts led to a delay of lens opacity progression. 56 This was an interesting observation because tea is very popular around the world, especially in China.…”
Section: Discussionmentioning
confidence: 99%
“…It strongly protects microglial cell-death. Mechanistically it can be explained that the catechin component up-regulates the Akt and mTOR phosphorylation and inhibits the hypoxia/reperfusion-induced autophagy in microglia [32]. Memory deficits and oxidative stress in cerebral ischemia-reperfusion is evident.…”
Section: Flavonoids Also Protect Non-hepatic Organsmentioning
confidence: 99%
“…These substances could trigger the focal oxidative stress response. It has been shown that after the onset of ischemia, oxidative stress response aggravates neuron injuries (6). This is deemed to be a major mechanism for injuries secondary to the ACIR (6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after the onset of ischemia, oxidative stress response aggravates neuron injuries (6). This is deemed to be a major mechanism for injuries secondary to the ACIR (6). Activated ROS facilitates the oxidative stress response induced by ACIR and further increases the expression of neuron-related apoptosis proteins in cerebral tissues (7).…”
Section: Discussionmentioning
confidence: 99%